Coronary artery air embolism: a potentially fatal complication of CT-guided percutaneous lung biopsy - Cheng, H-M (The British Institute of Radiology., 2010)
CT-guided transthoracic lung biopsy is becoming a widely accepted procedure for the diagnosis of pulmonary lesions. The rate of severe complications following such a procedure has been reported. Of these complications, air embolism is the most likely to be fatal. We report a case of right coronary air embolism resulting in myocardial infarction after a CT-guided percutaneous needle biopsy of the lung. The patient died from underlying malignant disease 4 months later.